Ritmos e ciclos no clima local de Cuiabá/Várzea Grande - MT : uma análise secular (1912 a 2012) - Silva, Maurinésia Pereira da (2015)
The main objective was to analyze trends and climatic oscillations in Cuiabá / Várzea Grande. The specific objectives were: to analyze the climate pace in Cuiabá / Várzea Grande in the period 1912-2012; study the climatic cycles duration and intensity over 100 years; investigate the variations of air temperature in the local climate; understand the possible relationship between temperature changes and population growth. The meteorological data used in this study were provided by INMET - National Meteorology Institute, operated by 9 Great Lowland Meteorological District. Organized themselves frames with all weather attributes. They were chosen for analysis two elements of weather, temperature and rainfall. Data were tabulated in annual, seasonal and monthly series from January 1912 to December 2012. The study area is located between parallels 14 ° and 16 ° South latitude and 54 ° meridian and 58 ° West longitude, at an altitude between 150-250 m about. The secular temporal analysis was grounded in conceptions of ritmanálise and holorrítmo, trying to understand reality as a whole in motion, physical, biological and social nature. The average annual temperature was 25.8 ° C, the average maximum was 32.6 ° C and the average minimum was 21.2 ° C. They identified two periods of increasing temperature trend, a first period that begins in the decade of 20 and extends until the end of the 60s and a second period starting in the 70s lasting until the end of series. The average annual rainfall was 1382.8, being subject to greater irregularities, non-rain cycles appear as evident as in the temperatures, long cycles are generally interspersed by variations in short time intervals of 1 to 4 years. It is likely that the trend of increase in temperature values was influenced by urbanization of Cuiabá / Várzea Grande, to the extent that the population grew average temperature also increased from 1970 to 2012, being the longest period trend temperature rise. Periods of strong temperature rise at the beginning of the series until the '20s are probably due to a combination of astronomical and planetary climate controls.